In Vitro and In Vivo Effects of Suppressor of Cytokine Signalling 7 Knockdown in Breast Cancer: The Influence on Cellular Response to Hepatocyte Growth Factor. (4th August 2014) - Sasi, Walid; Ye, Lin; Jiang, Wen G.; Sharma, Anup K.; Mokbel, Kefah
Abstract : Purpose . Suppressor of cytokine signaling 7 (SOCS7) is a member of the SOCS family and is known to interact with phospholipase C γ -1 (PLC γ -1), a key downstream mediator of the hepatocyte growth factor (HGF)/C-MET axis. Here, we report our observations of the effect of knocking down SOCS7 gene on the behaviour of breast cancer cells both in vitro and in vivo and to elucidate whether this involves HGF/C-MET pathway using the PLC γ -1 blocker U73122. Methods . MCF7 and MDA-MB-231 breast cancer cells were transfected with anti-SOCS7 ribozymal transgene, to create sublines with SOCS7 knockdown. The in vitro growth and migration of the cells were evaluated in basic conditions and with HGF and U73122 treatment using growth assays, scratch-wound, and electrical cell impedance sensing (ECIS) migration assays. MCF7 and MDA-MB-231 in vivo tumour xenograft growth were also studied. Results . Basal in vitro growth and migration of both cellular lines and the in vivo MCF7 xenograft growth were significantly enhanced with SOCS7 knockdown. In vitro HGF treatment has further influenced the growth and migration when SOCS7 gene was knocked-down in both cellular lines ( P < 0.05 ) . PLC γ -1 pharmacological inhibition of the HGF/C-MET cascade during their in vitro growth and migration seemed to only occur when SOCS7 gene was knocked down. Conclusions . We report a unique regulatory role for SOCS7 in controlling the malignant behaviour of breast cancer lines MCF7 and MDA-MB-231 in vitro and the MCF7 tumour xenografts in vivo . We also report a regulatory role for SOCS7 during the in vitro HGF-induced growth and migration in these cells as HGF treatment and SOCS7 loss have synergistically enhanced these functions. This SOCS7 knockdown-attributed effect could be due to a precise anti-PLC γ -1 role.